FORMULASI HARD CANDY DARI SARI BUAH JERUK NIPIS (Citrus aurantifolio), MADU (Mell depuratum) DAN KAYU MANIS (Cinnamomum burmanii) BERDASARKAN PERBEDAAN SIRUP GLUKOSA - Yulia, Mega; Azra, Fadhilla Putri; Ranova, Riki (Jurnal Riset Kefarmasian Indonesia, 2022)
Lime is a fruit that is widely used by people for treatment cough. For efficiency use of lime, it can processing to product that easier for using such as hard candy. This study aims to determine the results of physical tests and panelists preference for hard candies made from lime juice, honey and cinnamon. The method used is an experimental method by combining lime juice, honey, cinnamon and varying glucose syrup as a candy forming ingredient. Physical evaluation of each formula which includes analysis of water content and ash content, also hedonic test of 3 formulas to 100 panelists. The results of the physical evaluation carried out on the 3 formulas showed that all formulas met the quality requirements of SNI 3547.1:2008 hard candy for water content and ash content, also the results of the hedonic test using non parametric SPSS showed that there was a significant effect on taste and texture where formula III was the most preferred by panelist.